CEO emotional stability and firm innovation - LIU, Manli (Institutional Knowledge at Singapore Management University, 2024)
This dissertation aims to examine whether and how CEO emotional stability influences firm innovation. I argue that CEO emotional stability enables firms to create a friendly innovation climate within the firm as well as secure resources from external stakeholders, thus helping firm innovation. Moreover, CEO education, slack resources, firm age, and market complexity strengthen the relationship between CEO emotional stability and firm innovation. Two-wave surveys are conducted to collect the data to test the hypotheses. This dissertation aims to extend the literature on emotional stability as well as innovation from the upper echelons perspective.